Issue of depleting fish population - Mumbai Archive Project Team (Jio Institute, 2024)
Koli fishermen have been struggling with depleting fish populations caused by environmental degradation and overfishing. To find more fish, they venture further out at sea, where rare species like tiger sharks, whale sharks, sea turtles, stingrays, and sawfish accidentally become bycatch.